(untitled) (Bangladesh Journal of Botany, 2008)
Neurymenia fraxinifolia (Mert.) J. Ag. a marine red alga has been described and illustrated for the first time from St. Martin’s Island, Bangladesh. Key words: Neurymenia fraxinifolia, Marine red alga, New record, Bangladesh doi:10.3329/bjb.v36i1.1552 Bangladesh J. Bot. 36(1): 81-83, 2007 (June)